Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0033095
|View full text |Cite
|
Sign up to set email alerts
|

Early Interleukin-6 and Slope of Monocyte Human Leukocyte Antigen-DR: A Powerful Association to Predict the Development of Sepsis after Major Trauma

Abstract: Objective Major trauma is characterized by a pro-inflammatory response, followed by an immunosuppression. Recently, in trauma patients, the lack of recovery of monocyte Human Leukocyte Antigen DR (mHLA-DR, a biomarker of ICU-acquired immunosuppression) between days 1–2 and days 3–4 has been demonstrated to be independently associated with sepsis development. The main objective of this study was to determine whether early measurements of IL-6 (interleukin-6) and IL-10 plasma concentrations (as mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 65 publications
(77 reference statements)
8
76
1
2
Order By: Relevance
“…24 Meisel et al 20 and Schefold et al 25 demonstrated that awareness of the levels of mHLA-DR may help in guiding immunomodulatory therapy, shortening mechanical ventilation time and the duration of hospital stay. In recent years, several studies have shown that mHLA-DR is a valuable factor that can predict the outcomes of subjects with sepsis, severe pancreatitis, non-small cell lung cancers, cirrhosis, and secondary infections [3][4][5][6][7][8] ; some studies concluded otherwise, as the investigators suggested that mHLA-DR is not an independent factor that affects the outcomes of subjects and pointed out the limitations of flow cytometer examinations. [9][10][11] The immune system plays an important role in the development and progression of pneumonia, and mHLA-DR is a widely accepted biomarker that can reflect the immune functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Meisel et al 20 and Schefold et al 25 demonstrated that awareness of the levels of mHLA-DR may help in guiding immunomodulatory therapy, shortening mechanical ventilation time and the duration of hospital stay. In recent years, several studies have shown that mHLA-DR is a valuable factor that can predict the outcomes of subjects with sepsis, severe pancreatitis, non-small cell lung cancers, cirrhosis, and secondary infections [3][4][5][6][7][8] ; some studies concluded otherwise, as the investigators suggested that mHLA-DR is not an independent factor that affects the outcomes of subjects and pointed out the limitations of flow cytometer examinations. [9][10][11] The immune system plays an important role in the development and progression of pneumonia, and mHLA-DR is a widely accepted biomarker that can reflect the immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies over the past few years have demonstrated that monocyte human leukocyte antigen-DR (mHLA-DR) is a potential biomarker in predicting the outcomes of subjects with certain diseases (including sepsis, severe pancreatitis, non-small cell lung cancer, cirrhosis, and secondary infection), [3][4][5][6][7][8] although some studies have contrasting results. [9][10][11] The immune system plays an important role in the development, progression, and prognosis of pneumonia, 12 which suggests that this widely accepted immune function-related biomarker may predict outcomes in patients with severe pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6: (1) ARDS; two studies [37,45] could not relate ARDS to IL-6 concentration alterations, whereas two other studies [48,51] found a positive correlation (Table 2); (2) Sepsis; five studies [35,41,46,47,53] found an increased IL-6 production to be predictive for the development of sepsis, whereas five other studies [28,29,38,39,55] did not (Table 3); (3) MODS; all five prospective cohort studies [3,28,34,46,51] concluded that IL-6 is markedly increased in the early development of MODS ( Dekker ABE et al . Do cytokines predict polytrauma outcome IL-10: (1) Three studies, two prospective [54,57] and one retrospective [14] , could not relate the serum IL-10 concentrations to the development of ARDS.…”
Section: Value Of Main Cytokine Concentrations For Predicting Complicmentioning
confidence: 98%
“…Polymorphisms of the tumor necrosis factor-encoding gene (Majetschak et al, 2002;O'Keefe et al, 2002) and interferon-gamma-encoding gene (Stassen et al, 2002) have also been investigated. Gouel-Cheron et al (2012) found that a high interleukin-6 (IL-6) concentration and a persistent decrease in monocytic human leukocyte antigen DR (mHLA-DR) expression are indicators for development of sepsis. Microarray technology allows a widely used gene expression profile method for exploring molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%